The optimal transplantation strategy of umbilical cord mesenchymal stem cells in spinal cord injury: a systematic review and network meta-analysis based on animal studies - Yubao Lu; Wei Zhang; Zhenming Tian; Qian Liang; Chenrui Liu; Yingjie Wu; Liangming Zhang; Limin Rong (Stem Cell Research & Therapy, 2022)
Abstract Objective Umbilical cord mesenchymal stem cells (UCMSCs) have great potential in the treatment of spinal cord injury. However, the specific therapeutic effect and optimal transplantation strategy are still unclear. Therefore, exploring the optimal treatment strategy of UCMSCs in animal studies by systematic review can provide reference for the development of animal studies and clinical research in the future. Methods Databases of PubMed, Ovid-Embase, Web of Science, CNKI, WanFang, VIP, and CBM were searched for the literature in February 11, 2022. Two independent reviewers performed the literature search, identification, screening, quality assessment, and data extraction. Results and Discussion A total of 40 animal studies were included for combined analysis. In different subgroups, the results of traditional meta-analysis and network meta-analysis were consistent, that is, the therapeutic effect of high-dose (≥ 1 × 106) transplantation of UCMSCs was significantly better than that of low dose (< 1 × 106), the therapeutic effect of local transplantation of UCMSCs was significantly better than that of intravenous transplantation, and the therapeutic effect of subacute transplantation of UCMSCs was significantly better than that of acute and chronic transplantation. However, in view of the inherent risk of bias and limited internal and external validity of the current animal studies, more high-quality, direct comparison studies are needed to further explore the optimal transplantation strategy for UCMSCs in the future.